Conical liquid sheet morphology and 3D droplet distribution of aviation kerosene pressure-swirl spray with digital off-axis holography. (July 2023) - Wang, Lei; Wu, Yingchun; Zhang, Letian; Wang, Donghui; Yin, Jun; Lin, Wenhui; Song, Ge; Wu, Xuecheng; Huang, Yong
Abstract: In this study, the test performance of high-resolution digital off-axis holography for the non-spherical droplet characteristics and spatial distribution in the primary breakup region of a pressure-swirl nozzle were experimentally investigated, with spatial resolution of 4 . 5 μ m and 3 . 0 μ m . The field of interest (FOI) was restricted within 9 mm downstream of the nozzle outlet, where the primary and some secondary breakup processes take place. The liquid investigated here is RP-3 kerosene, and the injection pressure and liquid temperature were controlled in the range of 0.5 ∼ 1.0 MPa and 250 ∼ 291 K separately. Clear spray morphology and deformed droplet image were obtained through the holographic reconstruction process. Droplet extraction criteria were proposed to distinguish deformed droplets from ligaments. The overall drop size and ellipticity distribution were quantified and discussed. The results show that the overall drop size distributions near the nozzle are also typical single-peaked curves. The proportions of non-spherical droplet increase as the fuel pressure and temperature increase. The spatial Sauter mean diameter (SMD) distributions of spray at different positions downstream of the nozzle were calculated, with the grid size of 1 × 1 × 1 mm 3, showing the doughnut-like annular SMD and droplet number distribution profiles of the hollow conical spray. As the temperature and fuel pressure decrease, SMD distribution becomes uneven and larger. Fine droplets exist in the region where the perforation and primary breakup process occur, and the SMD increases over the axial distance due to the breakup process of ligaments near the nozzle. Results also prove that digital off-axis holography presented here is expected to realize the 3D viewing of the conical liquid sheet and statistical quantification of the droplet where primary and secondary breakup processes mainly occurred. Graphical abstract: Highlights: High-resolution DOH observed curved stripes in the conical liquid sheet image, which were attributed to the surface waves on the sheet. The droplets were distinguished from ligaments and liquid sheets in the breakup region, and the spatial SMD evolution was analyzed.